2016
DOI: 10.3233/thc-161220
|View full text |Cite
|
Sign up to set email alerts
|

Trial of real-time locating and messaging system with Bluetooth low energy

Abstract: Trial applications using BLE on iPhones worked well for patient tracking, and messaging in indoor environments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Authors indicated the need for more precise studies in this field. Other research was performed in the same area and it was a pilot study prepared to serve as a guide for developers of applications (for software as part of localization) and as help to identify potential research problems and future products [9]. Bluetooth location systems were also studied in terms of big data process environment [10] and was taken as a reference point for comparison with ZigBee solutions, which are similar to Bluetooth technology [11].…”
Section: Bluetooth In Constructionmentioning
confidence: 99%
“…Authors indicated the need for more precise studies in this field. Other research was performed in the same area and it was a pilot study prepared to serve as a guide for developers of applications (for software as part of localization) and as help to identify potential research problems and future products [9]. Bluetooth location systems were also studied in terms of big data process environment [10] and was taken as a reference point for comparison with ZigBee solutions, which are similar to Bluetooth technology [11].…”
Section: Bluetooth In Constructionmentioning
confidence: 99%